Principal Management in Forming Teacher Character: Aligning School Governance with SDG 4 and SDG 8 - Al Hadi; Dewie Tri Wijayanti Wardoyo; Amrozi Khamidi (Journal of Current Studies in SDGs, 2026)
Objective: To examine the principal's management in shaping teacher character, which is the foundation for realizing a school culture with integrity and sustainability. Method: The research was conducted with a qualitative approach through a multi-site study design, involving observation, in-depth interviews with principals, teachers, and students, as well as document review. Data were analyzed using cross-case analysis techniques to reveal the principal's management patterns in shaping teacher character. This study aims to analyze: (1) Planning, (2) Organizing, (3) Implementation; and (4) Supervision of the principal in shaping teacher character in managing schools at SMP Negeri 3 Krian, Sidoarjo.  Results:  1) Planning: The Principal of SMP Negeri 3 Krian applies flexible, contextual, and participatory methods through intensive communication between school members. 2) Organizing: The Principal of SMP Negeri 3 Krian applies a collaborative and humanistic approach that prioritizes interpersonal communication and a sense of family to increase teachers' sense of belonging. 3) Implementation: The Principal of SMP Negeri 3 Krian applies a persuasive, cultural, and humanistic approach through informal communication to build a harmonious work environment. 4) Supervision: The Principal of SMP Negeri 3 Krian chooses a humanistic and interpersonal approach through informal observation and open personal coaching. Novelty: The research places the context of teacher character formation as the primary focus, not merely as a supporting variable for improving competence or performance. This focus offers a novel contribution because teacher character is the foundation for creating a school culture of integrity and sustainability for SDG 4 and SDG 8.